2019
DOI: 10.1093/ckj/sfz179
|View full text |Cite
|
Sign up to set email alerts
|

Net ultrafiltration rate and its impact on mortality in patients with acute kidney injury receiving continuous renal replacement therapy

Abstract: Background Fluid overload, a critical consequence of acute kidney injury (AKI), is associated with worse outcomes. The optimal fluid removal rate per day during continuous renal replacement therapy (CRRT) is unknown. The purpose of this study is to evaluate the impact of the ultrafiltration rate on mortality in critically ill patients with AKI receiving CRRT. Methods This was a retrospective cohort study where we reviewed 139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 32 publications
4
25
0
Order By: Relevance
“…The results of this study were partly consistent with four previous studies [9][10][11][12]. Murugan and his colleagues found that in patients with volume overload > 5% and receiving renal replacement therapy, the 1-year mortality in patients with an NUF rate > 25 mL/kg/d was lower than that of < 20 mL/kg/d [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study were partly consistent with four previous studies [9][10][11][12]. Murugan and his colleagues found that in patients with volume overload > 5% and receiving renal replacement therapy, the 1-year mortality in patients with an NUF rate > 25 mL/kg/d was lower than that of < 20 mL/kg/d [9].…”
Section: Discussionsupporting
confidence: 91%
“…Murugan and his colleagues found that in patients with volume overload > 5% and receiving renal replacement therapy, the 1-year mortality in patients with an NUF rate > 25 mL/kg/d was lower than that of < 20 mL/kg/d [9]. Shahrzad found that in patients with AKI receiving CKRT, the NUF rate ≥ 35 mL/kg/d was associated with a lower 30-day mortality [10]. Two other studies found that, compared with an early NUF rate of < 1.01 mL/kg/h, an NUF rate of > 1.75 mL/kg/h was associated with increased mortality [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study demonstrated that a higher net ultrafiltration rate was associated with a higher mortality rate ( 31 ). However, another study revealed an association between higher net ultrafiltration and improved survival rate ( 32 ). Similarly, the association between net ultrafiltration rate and renal recovery rate has yet to be established ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation and management of uid balance are key challenges when caring for critically ill patients requiring renal replacement therapy (RRT) [1,2]. Despite considerable advances in the assessment of dialysis adequacy with respect to solute removal and data suggesting that net ultra ltration may be associated with the outcomes [3][4][5], there is currently no speci c measure of adequacy for uid removal [6,7]. Intradialytic hypotension is a common complication associated with RRT; it may be associated with the ultra ltration rate and can cause further ischemic injury to the recovering kidneys, thereby potentially reducing the probability of renal recovery [4,8].…”
Section: Introductionmentioning
confidence: 99%